A Role of the 9-Aminoacridines and their Conjugates in a Life Science - Sebestik, Jaroslav; Hlavacek, Jan; Stibor, Ivan (Current Protein and Peptide Science, 2007)
The 9-aminoacridines play an important role in medicine. They were applied first in a treatment of protozoal infections in the beginning of the last century. Recently, it has been shown that the 9-aminoacridines are successful candidates for treatment of cancer, viral and prion diseases. Their conjugation with biomolecules such as peptides and proteins may modulate their activity, bioavailability and applicability. This review deals with the synthesis of 9-aminoacridine, its conjugation with variety of molecules and utilization of such conjugates in several fields of science.
Keywords: proteins